Zfat-Deficiency Results in a Loss of CD3ζ Phosphorylation with Dysregulation of ERK and Egr Activities Leading to Impaired Positive Selection - Ogawa, Masahiro (Public Library of Science, 2013)
The human ZFAT gene was originally identified as a susceptibility gene for autoimmune thyroid disease. Mouse Zfat is a critical transcriptional regulator for primitive hematopoiesis and required for peripheral T cell homeostasis. However, its physiological roles in T cell development remain poorly understood. Here, we generated Zfat (f/f)-LckCre mice and demonstrated that T cell-specific Zfat-deletion in Zfat (f/f)-LckCre mice resulted in a reduction in the number of CD4(+)CD8(+)double-positive (DP) cells, CD4(+)single positive cells and CD8(+)single positive cells. Indeed, in Zfat (f/f)-LckCre DP cells, positive selection was severely impaired. Defects of positive selection in Zfat-deficient thymocytes were not restored in the presence of the exogenous TCR by using TCR-transgenic mice. Furthermore, Zfat-deficient DP cells showed a loss of CD3ζ phosphorylation in response to T cell antigen receptor (TCR)-stimulation concomitant with dysregulation of extracellular signal-related kinase (ERK) and early growth response protein (Egr) activities. These results demonstrate that Zfat is required for proper regulation of the TCR-proximal signalings, and is a crucial molecule for positive selection through ERK and Egr activities, thus suggesting that a full understanding of the precise molecular mechanisms of Zfat will provide deeper insight into T cell development and immune regulation.